Identificando e classificando o perfil de leitores dos graduandos em Química licenciatura da Universidade Federal de Sergipe (UFS) - Andrade, Tatiana Santos (2014)
Reading is considered by many scholars essential to assist the individual in the construction of knowledge and the acquisition of meanings instrument, because, according to Kleiman & Moraes (2003), the improvement in the ability to read also results in improving the ability to learn, going Apart from receiving information, so we believe it is very important work to read in chemistry classes in order to promote a closer apprehension of knowledge of scientific literacy. Studies show that science teachers have no theoretical knowledge to work with their students to read from the interactive - constructive model (Queiroz, 2004). Thus, in this study we sought to identify the profile of readers of the students of the degree in chemistry in order to understand the views they had about reading in teaching chemistry and also provide moments of reading mediated teacher trainer and assisted by researcher using the reading strategies of Solé (2008), so we could classify the profile of undergraduate readers. From these moments of reading, we seek to identify the language used by undergraduates and also if they could understand the texts read. Respondents attending the disciplines of Chemistry Education Research and Methodology and Instrumentation for the Teaching of Chemistry at the UFS. This identification was designed to understand what types of reading were performed by undergraduates and how they conceived of reading in teaching chemistry. Used as an instrument of data collection, an open questionnaire on the topic and a scientific article taken from the New School Chemistry magazine. Data analysis was done by interpreting briefs and statements prepared by researchers, using as a benchmark for analyzing the ideas of Bakhtin (2011) and Solé (2008), which were also used as a theoretical framework. This review process was intended to question the meanings set out in its different forms of production which can be verbal or non-verbal, it is sufficient that its materiality sense to bring its interpretation. From the data analysis, we understand that reading is undervalued in the training of undergraduates in Chemistry from UFS process, and it corroborates a posture of passive reader, in other words, one that does not interact with the text and that only the read superficially (Solé, 2008).